Post-Resuscitation Hemodynamics and Relationship to the Duration of Ventricular Fibrillation - Menegazzi, James J. (2008)
OBJECTIVE: We have observed consistent hemodynamic patterns after restoration of spontaneous circulation (ROSC) after ventricular fibrillation (VF) cardiac arrest. We sought to characterize the time-course of these patterns, and to determine whether these differed based on duration of the VF insult. METHODS: We performed a retrospective review of data from a randomized animal experiment that was conducted in an AAALAC-approved animal laboratory. We used mixed-breed domestic swine of either sex. Animals were anesthetized and instrumented for continuous recording of ECG and blood pressures. VF was induced electrically and allowed to progress for various times ranging from brief (22s) to moderate (less than 3 minutes) to prolonged (3 to 10 minutes). All animals were initially shocked (150J) up to three times. If ROSC was not achieved on the 3 initial shocks, a standardized treatment protocol was followed. We defined cardiovascular collapse as a SBP < 90 mmHg sustained for one minute. For statistical purposes, we classified animals as having VF of <3 minutes, or >3minutes duration. Data were analyzed with Fisher’s exact test and survival analysis. RESULTS: A hyperdynamic phase, consisting of very high blood pressures and tachycardia, was seen in all animals immediately after ROSC. This lasts from 1 to 4 minutes. Post-resuscitation cardiovascular collapse occurred in 2/7 (29%) animals in the <3 minute group and 13/14 in the >3 minute group (93%) p=0.006. Onset of cardiovascular collapse was highly related to duration of VF (log-rank p=0.004). CONCLUSIONS: There are two distinct phases of hemodynamic change after resuscitation of VF. The first phase is a brief hyperdynamic phase. The second phase is either stabilization or cardiovascular collapse. When VF is brief, blood pressures often return to normal without exogenous support. When VF was prolonged animals were rescued with exogenous pressor. Healthcare providers should be prepared to provide pressor support for patients having ROSC after prolonged VF.